The Effect of Dowel Space on the Bond Strengths of Fiber Posts - Jorge PerdigËœao, DMD, MS, PhD;1 George Gomes, DMD;2 (Journal of Prosthodontics, 2007)
The purpose of this study was to evaluate the effect of the degree of mismatch between post space and post diameters on the bond strength of a fiber-reinforced resin post